A rotating sprayer for air pre-cooling with atomized water injection in air-cooled heat exchangers - Kritzinger, H. P.(Herculus Petrus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1999.